Does Financial Liberalization Foster Economic Growth? Empirical Evidence from ASEAN-6 Countries - Kumari Selvarajan, Sonia; Ab-Rahim, Rossazana; Awg-Marikan, Dyg-Affizzah (International Journal of Engineering and Technology, 2018)
This paper aims to investigate the impacts of financial liberalization towards the economic growth in ASEAN-6 countries (Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam) throughout the study period of 1990 to 2015 by employing the Pooled Mean Group (PMG) estimations technique. The proxies for financial liberalization are the domestic private credit (DPC) and the stock market capitalization (SMC); while the indicator for economics growth is represented by gross domestic products (GDP) growth per capita. The results show greater DPC foster the ASEAN-6 economic growth in the long-run and more relaxed loans as well as non-equity securities regimes of the private sector provide greater opportunity and eventually trigger the development of the private sector which result in a healthier economy. Interestingly, the SMC results confirm the positive relationship between financial liberalization and economic growth of ASEAN-6. Hence, the results offer an evidence of the growth-stimulating effect of financial liberalization among ASEAN-6 countries.Â Â